Social Media for Knowledge Sharing in Automotive Repair - Finkbeiner, Patric (Springer International Publishing : Imprint: Springer, 2017)
This book explores, describes and explains the predictors essential for the acceptance of social media as a digital platform to share professional knowledge in the field of automotive repair in Germany. It reports a rigorous literature review covering key elements of social media, knowledge management and technology acceptance studies. The book assumes a pragmatist approach and applies mixed methods in an exploratory sequential design, combining qualitative and quantitative methods to ensure robust collection and analysis of the collected data. Based on a survey on German automotive repair shops, the author provides a framework, for various stakeholders, to comprehend the motivations for knowledge sharing for automotive repair professionals in Germany. This book not only adds to the existing academic body of knowledge but also provides implications for industry and legislation on a European scale. .